Application of sprinkler cooling within the bunch zone during ripening of Cabernet Sauvignon berries to reduce the impact of high temperature. (2nd December 2016) - Caravia, L.; Pagay, V.; Collins, C.; Tyerman, S.D.
Abstract: Background and Aim: High temperature stress has been linked to detrimental effects on berry composition during ripening. This study aimed to assess the impact of an evaporative cooling system located inside the grapevine canopy to mitigate extreme temperature effects on grape berry composition during ripening. Methods and Results: During three seasons (2012 to 2015), an intra‐canopy sprinkler system at the bunch zone was tested on Cabernet Sauvignon vines. The system cyclically sprayed (20 s/10 min) for an air temperature above 38°C, cooling the air inside the canopy by 3 to 5°C. This is in agreement with an air cooling simulation model. The relative humidity in the canopy also increased in the sprinkler‐cooled canopy. No differences were detected in TSS, although sugar per berry was significantly higher in treated vines because of increased berry mass. There was a tendency for higher anthocyanins and phenolic substances per berry in cooled berries measured from two seasons and higher concentration of anthocyanins in wine from cooled fruit measured only in one season. We define indices that can be used to assess the efficiency of sprinkler cooling and to demonstrate the high efficiency of intra‐canopy sprinklers compared to other systems. Conclusion: Despite cooling operating only over a small duration of the ripening period, the increased berry mass indicates that high temperature, even for a short period, has a profound effect on berry growth. Other berry compositional properties and wine, however, were not impacted. Significance of Study: This research demonstrates the potential of an efficient intra‐canopy sprinkler system to reduce heat stress during ripening.